Evidence from the Skilled-Unskilled Canadian Wage Index - Devoretz, D.J.; Reed, Clyde (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
The authors critically reassess the standard view that Canada's skilled-unskilled wage differential has collapsed over the past four decades.